Post-traumatic stress symptoms and cognition in children exposed to motor vehicle accident trauma. Issue 4 (18th May 2020) - Malarbi, Stephanie T.; Muscara, Frank; Barnett, Peter L. J.; Palmer, Cameron S.; Stargatt, Robyn
ABSTRACT: Research investigating the cognition of children exposed to non-familial trauma is scarce and the effects of post-traumatic stress symptoms in this population remain unclear. Thus, this research aimed to investigate the cognition of children exposed to motor vehicle accidents given the high incidence of this trauma globally. It was hypothesized that children with post-traumatic stress symptoms (PTSS; i.e., children with subthreshold or a full diagnosis of PTSD; n = 6) would perform significantly worse on cognitive measures compared to children exposed to trauma only (TO; i.e., children with very minimal or no PTSS; n = 10) and a healthy control group ( n = 19). Analyses showed children with PTSS demonstrated significantly poorer perceptual reasoning F (2, 32) = 7.21, p = .01, partial η 2 = .31; verbal learning F (2, 32) = 3.87, p = .05, partial η 2 = .20; and delayed verbal memory F (2, 32) = 4.40, p = .05, partial η 2 = .22, compared to HCs. The magnitude of the differences between the groups was large. Differences in immediate verbal recall, executive functioning, and verbal intellectual abilities were moderate to large in magnitude, with the PTSS group performing worse than both groups, but these findings did not reach significance. Overall findings from this study provide further support for the notion that children exposed to non-familial trauma with significant PTSS display cognitive difficulties compared to healthy children.